2017
DOI: 10.1021/acsami.6b12949
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Interaction between Nafion Ionomer and Surface Functionalized Carbon Black Using Both Ultrasmall Angle X-ray Scattering and Cryo-TEM

Abstract: In making a catalyst ink, the interactions between Nafion ionomer and catalyst support are the key factors that directly affect both ionic conductivity and electronic conductivity of the catalyst layer in a membrane electrode assembly. One of the major aims of this investigation is to understand the behavior of the catalyst support, Vulcan XC-72 (XC-72) aggregates, in the existence of the Nafion ionomer in a catalyst ink to fill the knowledge gap of the interaction of these components. The dispersion of cataly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
81
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(87 citation statements)
references
References 35 publications
6
81
0
Order By: Relevance
“…25 For this reason, Pt/KB IW and Pt/KB TKK showed a mass activity of 249 ± 1 and 372 ± 29 A/g, while the Pt/KB PO and Pt/KB(NH x ) PO catalysts synthesized by the polyol method had lower mass activities of 220 ± 11 and 161 ± 2 A/g, respectively. The lower mass activity of the latter most likely arises from a better ionomer distribution of the KB(NH x ) support as shown in a previous publication, 15 where we argued that an increased interaction of the ionomer with the modified carbon black surface 33 would lead to a more homogeneous ionomer distribution, reaching more platinum particles and thus lowering their ORR mass activity. In addition, part of this effect may also derive from a somewhat larger fraction of Pt being deposited on the outer surface of the NH x -modified Ketjenblack due to a stronger Pt/support interaction during the deposition of Pt onto the surface-functionalized Ketjenblack.…”
Section: Catalystsupporting
confidence: 83%
“…25 For this reason, Pt/KB IW and Pt/KB TKK showed a mass activity of 249 ± 1 and 372 ± 29 A/g, while the Pt/KB PO and Pt/KB(NH x ) PO catalysts synthesized by the polyol method had lower mass activities of 220 ± 11 and 161 ± 2 A/g, respectively. The lower mass activity of the latter most likely arises from a better ionomer distribution of the KB(NH x ) support as shown in a previous publication, 15 where we argued that an increased interaction of the ionomer with the modified carbon black surface 33 would lead to a more homogeneous ionomer distribution, reaching more platinum particles and thus lowering their ORR mass activity. In addition, part of this effect may also derive from a somewhat larger fraction of Pt being deposited on the outer surface of the NH x -modified Ketjenblack due to a stronger Pt/support interaction during the deposition of Pt onto the surface-functionalized Ketjenblack.…”
Section: Catalystsupporting
confidence: 83%
“…Listing one, it strongly lowers zeta potential on nanotubes in isopropanol suspensions [28]. An excellent ionic conductivity of Nafion 117 ® is another advantage and leads to improvement of electrochemical response (i.e., double-layer capacitance) of dispersed nanotubes [40,41]. This is related to the formation of percolated water channels that facilitate proton transport via a vehicular mechanism, which was analyzed by small angle neutron scattering (SANS) [42].…”
Section: δV δPmentioning
confidence: 99%
“…It has been demonstrated that these different solution-phase morphologies directly impact cast film properties; [6][7][8][9][10][11][12][13][14] ionomers maintain a memory of these structures. 15 These solvent effects must also change the interactions driving ionomer-particle aggregation/stability in an ink, because different water:alcohol ratio inks each exhibit different aggregate sizes, 7,[16][17][18][19][20][21][22] and once dried, different CL morphology, water uptake, conductivity, etc.…”
Section: Introductionmentioning
confidence: 99%